(untitled) (Abhat Journal, 2025)
Yemeni historical sources have addressed the social situation in Mecca in the from 11th AH Century from various aspects, opening the door for comprehensive studies. These sources have discussed diseases that affected the residents of Mecca, as well as the demographic composition of Mecca and its internal and external factors. They have also explored some of the administrative corruption, customs and traditions prevalent in Meccan society in various aspects. All of this and more can be found in Yemeni sources that have been buried under dust and neglect, highlighting the need for attention and rehabilitation. This, in turn, would provide an opportunity to document the history of Mecca and other countries in most fields across different time periods.